Biosensors: Electrochemical Quantification of Escherichia coli with DNA Nanostructure (Adv. Funct. Mater. 25/2015). (July 2015) - Giovanni, Marcella; Setyawati, Magdiel Inggrid; Tay, Chor Yong; Qian, Hang; Kuan, Win Sen; Leong, David Tai
<x xml:space="preserve">Abstract</x> On page 3840, W. S. Kuan, D. T. Leong, and colleagues develop DNA nanopyramid‐based biosensing of Escherichia coli developed by using the highly specific sandwich immunoassay assembly. Low detection limits are obtained for E. coli lipopolysaccharides, bacteria lysate, and whole bacteria. This system can also distinguish the bacteria in a complex mixture while not getting interferences from the mixture components. (Protein molecules images: RCSB PDB. SG50 Logo ‐ "Singapore50.sg".)